Teddy Roosevelt and Leonard Wood : Partners in Command - Eisenhower, John S. D., 1922-2013 (Book collections on Project MUSE., 2014)
Theodore Roosevelt was a man of wide interests, strong opinions, and intense ambition for both himself and his country. When he met Leonard Wood in 1897, he recognized a kindred spirit. Moreover, the two men shared a zeal for making the United States an imperial power that would challenge Great Britain as world leader. For the remainder of their lives, their careers would intertwine in ways that shaped the American nation.